2019
DOI: 10.1371/journal.pntd.0007809
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence estimates for toxocariasis in people worldwide: A systematic review and meta-analysis

Abstract: BackgroundHuman toxocariasis is an important neglected disease. We performed a systematic review and meta-analysis study to estimate the global and regional prevalence of anti-Toxocara serum antibodies (referred to as ‘T-seroprevalence’) in human populations around the world.MethodsWe searched five international databases (PubMed, EMBASE, Web of Science, SciELO and Scopus) for seroprevalence studies published from 1 January 1980 to 15 March 2019. We used random effect models to calculate the overall T-seroprev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
128
5
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(183 citation statements)
references
References 48 publications
8
128
5
5
Order By: Relevance
“…Toxocariasis is a prevalent parasitic zoonosis worldwide, especially in the tropics and subtropics. This study was the first serological investigation of T. canis infection among schoolchildren in southern Thailand, with a prevalence rate of 58.2%, which was higher than the global seroprevalence (19.0%) and the pooled seroprevalence in Southeast Asia (34.1%) [20]. The rate of T. canis infection in this study was slightly higher than the rates in other countries in Asia, including the Philippines (49.0%) [14], Taiwan (57.5%) [27], Turkey (45.9%) [13], Korea (51.2%) [28], and Isfahan, Iran (45.9%) [16], whereas the rate was lower than those in some other parts of the world, including Nigeria (86.1%) [9] and the Republic of the Marshall Islands (86.8%) [10].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Toxocariasis is a prevalent parasitic zoonosis worldwide, especially in the tropics and subtropics. This study was the first serological investigation of T. canis infection among schoolchildren in southern Thailand, with a prevalence rate of 58.2%, which was higher than the global seroprevalence (19.0%) and the pooled seroprevalence in Southeast Asia (34.1%) [20]. The rate of T. canis infection in this study was slightly higher than the rates in other countries in Asia, including the Philippines (49.0%) [14], Taiwan (57.5%) [27], Turkey (45.9%) [13], Korea (51.2%) [28], and Isfahan, Iran (45.9%) [16], whereas the rate was lower than those in some other parts of the world, including Nigeria (86.1%) [9] and the Republic of the Marshall Islands (86.8%) [10].…”
Section: Discussionmentioning
confidence: 77%
“…In Western countries, the prevalence was 5.0% in the USA [17], 8.0% in Italy [18], and 16.0% in Greece [19]. A systematic review and meta-analysis revealed that the global seroprevalence of toxocariasis was 19.0%, with the highest rate in the African region (37.7%) and the lowest rate in the Eastern Mediterranean region (8.2%) [20]. Many factors have been proposed to be involved, including contact with dogs [11,15], children's age [21], and male sex [11,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Other than the publications mentioned above, we were not able to find more toxocariasis-related data either published or in the grey literature. Nonetheless, given that canine and human toxocariasis are prevalent in countries with similar climatic and socio-economic characteristics [ 6 ], we theorized that this parasitic disease is highly prevalent in Honduras.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggests that this infection may partially account for cognitive deficits and other neurological complications seen among socioeconomically disadvantaged children [ 1 , 4 ]. There is a strong body of research from Europe and South America and a recent interest resurgence in the United States [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report on two children with undiagnosed Toxocara canis infestation that developed pulmonary symptoms during intensive high-risk neuroblastoma treatment. Toxocariasis is one of the most common zoonoses in the world, and its IgG seroprevalence might be roughly estimated at up to 20% worldwide and up to 10% in Europe, with wide variance between studies and regions [ 1 , 2 ]. Toxocariasis is caused by infestation of humans by ascarid larvae belonging to the Toxocara genus from dogs and cats, and has varied clinical manifestations including systemic and compartmentalized syndromes as well as asymptomatic cases.…”
Section: Introductionmentioning
confidence: 99%